Unusual distortions about Tl and Pb in PbTe:Tl. Issue 2 (21st December 2012) - Bridges, F.; Keiber, T.; Medling, S.; Sales, B.C.; Stanek, Christopher R.; Nikl, Martin; Kovács, László; Greulich‐Weber, Siegmund
Abstract When the well know thermoelectric PbTe is doped with a few percent Tl, the figure of merit, ZT = S2 σ /κ, is dramatically improved (here S is the Seebeck coefficient, σ the electrical conductivity and κ the thermal conductivity). Tl is a valence skipper with valences of +1 and +3 and replaces Pb(+2) in PbTe. Further Tl(+1) has a lone electron pair; consequently, the atom is asymmetric and large local distortions are expected if Tl(+1) is present. Here we we present Extended X‐ray Absorption Fine Structure (EXAFS) data for 1% Tl doped PbTe at the Tl and Pb L3 edges and at the Te K edge, to probe the local structure about the dopant, and host atoms. At 10 K the local structure about Pb and Te is well ordered, although disorder of the Pb‐Te (Te‐Pb) pair distribution function (PDF) increases rapidly with increasing T. In contrast the environment around Tl is more disordered even at 10 K within the well ordered host material. This indicates a large variation of the Tl‐Te bond lengths presumably as a result of the presence of some Tl(+1). This increased local disorder will result in additional electron and phonon scattering. We discuss possible models for the disorder about Tl and for PbTe at higher temperature for which neutron PDF measurements suggest Pb moves off‐center (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)